Agriculture in 2050: Recalibrating Targets for Sustainable Intensification - HUNTER, MITCHELL C.; SMITH, RICHARD G.; SCHIPANSKI, MEAGAN E.; ATWOOD, LESLEY W.; MORTENSEN, DAVID A. (Bioscience, 2017)
The prevailing discourse on the future of agriculture is dominated by an imbalanced narrative that calls for food production to increase dramatically—potentially doubling by 2050—without specifying commensurate environmental goals. We aim to rebalance this narrative by laying out quantitative and compelling midcentury targets for both production and the environment. Our analysis shows that an increase of approximately 25%–70% above current production levels may be sufficient to meet 2050 crop demand. At the same time, nutrient losses and greenhouse gas emissions from agriculture must drop dramatically to restore and maintain ecosystem functioning. Specifying quantitative targets will clarify the scope of the challenges that agriculture must face in the coming decades, focus research and policy on achieving specific outcomes, and ensure that sustainable intensification efforts lead to measurable environmental improvements. We propose new directions for research and policy to help meet both sustainability and production goals.